Diversity and abundance of heterobranchs (Mollusca, Gastropoda) from the mesophotic and bathyal zone of the Mediterranean Sea. Issue 1 (31st December 2022) - Toma, M.; Betti, F.; Bavestrello, G.; Cattaneo-Vietti, R.; Canese, S.; Cau, A.; Andaloro, F.; Greco, S.; Bo, M.
Abstract: The occurrence, relative abundance and bathymetric distribution of the deep Mediterranean heterobranch fauna were evaluated as a result of an extensive visual census down to 1825 m depth, carried out along the western Italian coasts, covering a latitudinal range of about 600 nautical miles. Observations were conducted using Remotely Operated Vehicles (ROVs) in 551 sites, focusing on the deepest part of the continental shelf, the shelf edge and the upper bathyal zone. The analysis of over 508 hours of video footage and more than 27, 000 high-resolution photographs allowed to explore about 594, 000 m 2 of rocky outcrops and nearby soft seafloors in four main coastal areas (Ligurian Sea, north-central Tyrrhenian Sea, southern Tyrrhenian Sea, and Sicily Channel) and twelve offshore seamounts. Thirty-six species of heterobranchs, for a total of 559 records, were identified. Sixteen were only sporadically spotted (< 1% of the total observations), while three ( Paraflabellina ischitana, Tritoniidae nd and Peltodoris atromaculata ) contributed each for more than 10% of the records. An extension of the known Mediterranean bathymetric distribution was reported for 80% of the observed species, with many typically shallow-water taxa being also found in mesophotic environments (40–200 m). The observed marked decrease in diversity and abundance suggested that Mediterranean heterobranchs are mainly a coastal benthic group. From the geographical point of view, the heterobranch fauna present in the Ligurian Sea appeared significantly different from that observed in the Tyrrhenian Sea and the Sicily Channel, and this latitudinal pattern was discussed. Particular attention was given to single out the bathymetric distribution of the food sources of the most frequently observed species, supporting stenophagy as a limiting factor for their colonisation of the deep sea.